Perkembangan Baitul Maal Wat Tamwil (BMT) Pada Periode 2014-2019 di Indonesia - Josua Adrio Sihombing; Jumay Eferta Tarigan; Natasia Theofani Margaret; Pitri Aulia Usman Lubis; Rana Nabillah; Riris Hotma Roito Manalu; Jacob Kuntuy (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Baitul Maal Wat Tamwil (BMT), as an Islamic microfinance institution, plays a crucial role in enhancing financial inclusion and empowering the economy of communities in Indonesia. By combining the functions of Baitul Maal for managing social funds and Baitul Tamwil for productive financing, BMT supports the growth of small and medium-sized enterprises and reinforces the principles of Islamic finance. This study examines the development of BMT in Indonesia during the period from 2014 to 2019 through a descriptive qualitative approach and literature review. The results indicate that the number of BMTs increased from around 4,000 units in 2014 to 4,500 units in 2018, with a significant contribution to promoting financial inclusion, especially for the lower-middle-income population. However, BMT faces challenges related to complex regulations, unintegrated data collection, and the need for enhanced transparency and accountability in its operations. This study aims to provide insights for better policy development to support the role of BMT.